Analytical Study of the International Economic Policies of Iran and Russia: A Move to Bilateral Cooperation under Sanctions - Ismael Rezaeinejad (Review of Business and Economics Studies, 2022)
The high inflation, unemployment rate, and production reduction are apparent characteristics of the current state of Iran's economy. Therefore, studying solutions for the relationship with other countries and broader exposure to international trade is crucial. However, in the situation of sanctions, few countries can establish a free economic relationship with Iran, and Russia is one of the most important countries in this context. The article aims to investigate the history and perspectives of the economic cooperation between Iran and Russia. The paper uses an analytical — descriptive method to depict the international economic policies of Iran and Russia and the opportunities and challenges in their bilateral economic cooperation to pass unfair international sanctions and pursue economic development. The author concludes that although the political dimension was dominant in Iran and Russia relations, the two countries have realized the importance of bilateral economic ties, trying to improve the existing connections, which have shown the positive future of cooperation between the two countries.